An adverse outcome pathway-based approach to assess aurantio-obtusin-induced hepatotoxicity. (August 2022) - Hu, Manjiang; Zhong, Yizhou; Liu, Jun; Zheng, Shaozhen; Lin, Li; Lin, Xi; Liang, Boxuan; Huang, Yuji; Xian, Hongyi; Li, Zhiming; Zhang, Bingli; Wang, Bo; et al.
Abstract: Cassiae semen (CS), a traditional Chinese medicine, has various bioactivities in preclinical and clinical practice. Aurantio-obtusin (AO) is a major anthraquinone (AQ) ingredient derived from CS, and has drawn public concerns over its potential hepatotoxicity. We previously found that AO induces hepatic necroinflammation by activating NOD-like receptor protein 3 inflammasome signaling. However, the mechanisms contributing to AO-motivated hepatotoxicity remain unclear. Herein, we evaluated hepatotoxic effects of AO on three liver cell lines by molecular and biochemical analyses. We found that AO caused cell viability inhibition and biochemistry dysfunction in the liver cells. Furthermore, AO elevated reactive oxygen species (ROS), followed by mitochondrial dysfunction (decreases in mitochondrial membrane potential and adenosine triphosphate) and apoptosis (increased Caspase-3, Cleaved caspase-3, Cytochrome c and Bax expression, and decreased Bcl-2 expression). We also found that AO increased the lipid peroxidation (LPO) and enhanced ferroptosis by activating cyclic adenosine monophosphate (cAMP)-protein kinase A (PKA)-cAMP response element-binding (CREB) pathway (increases in PKA, p-CREB, acyl-CoA synthetase long chain family member 4). Based on these results, we used an AOP framework to explore the mechanisms underlying AO's hepatotoxicity. It starts from molecular initiating event (ROS), and follows two critical toxicity pathways (i.e., mitochondrial dysfunction-mediated apoptosis and LPO-enhanced ferroptosis) over a series of key events (KEs) to the adverse outcome of hepatotoxicity. The results of an assessment confidence in the adverse outcome pathway (AOP) framework supported the evidence concordance in dose-response, temporal and incidence relationships between KEs in AO-induced hepatotoxicity. This study's findings offer a novel toxicity pathway network for AO-caused hepatotoxicity. Highlights: AO induces hepatotoxicity in the liver cells. AO induces apoptosis in the liver cells by ROS-mediated mitochondrial dysfunction. AO enhances LPO and contributes to ferroptosis in the liver cells. AO induces ferroptosis via ACSL4 through activation of cAMP-PKA-CREB pathway. This AOP framework has described mechanisms underlying AO-induced hepatotoxicity.